2012
DOI: 10.1007/s00392-011-0410-4
|View full text |Cite
|
Sign up to set email alerts
|

Gender’s impact on outcome in coronary surgery with minimized extracorporeal circulation

Abstract: Gender-related disparity in outcome still remains present after surgery with minimized extracorporeal circulation. However, female gender per se is not an independent risk factor for in-hospital mortality, but close attention should be paid on modifiable risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Those with a p-value <0.1 at Pearson's correlation chi-square, as well as age and sex, were added in the multivariate model. Since previous studies demonstrated that body surface area (BSA) is associated with a worse outcome post-CABG in female sex we used BSA instead of body mass index [13,14]. Because of the welldocumented surgical characteristics, a subanalysis was made regarding the type of grafts used during CABG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those with a p-value <0.1 at Pearson's correlation chi-square, as well as age and sex, were added in the multivariate model. Since previous studies demonstrated that body surface area (BSA) is associated with a worse outcome post-CABG in female sex we used BSA instead of body mass index [13,14]. Because of the welldocumented surgical characteristics, a subanalysis was made regarding the type of grafts used during CABG.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our results showed no differences in percentage of offpump CABG between men and women and no benefit of off-pump CABG for the composite endpoint in both men and women. Previous studies showed an increased risk of adverse outcome in women for CABG on cardiopulmonary bypass, compared to off-pump CABG [4e8, 10,14]. The majority of prior studies included emergency CABGs whereas we excluded these unstable patients, which makes it difficult to directly compare results [4e8,10e15].…”
Section: Discussionmentioning
confidence: 99%
“…To avoid the problems mentioned above and yet capture the universal quality of care, we used CABG service volumes, risk-adjusted infection rates, and inpatient mortality rates to represent the structure and outcome dimensions respectively. We then applied k-means clustering to help in categorizing quality of care.Relationships among income status, patterns of quality of care, and healthcare outcomesPrevious studies regarding the inequality of CABG outcomes have primarily emphasized differences in gender [46,47] and ethnicity [3,48]. Few studies have discussed the influence of healthcare providers [49].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies regarding the inequality of CABG outcomes have primarily emphasized differences in gender [46,47] and ethnicity [3,48]. Few studies have discussed the influence of healthcare providers [49].…”
Section: Discussionmentioning
confidence: 99%
“…There are also gender 80 and racial disparities 10 in the availability of cardiac surgery care that influence outcomes. Additionally, sociodemographic influences can impair cardiac surgery outcomes.…”
Section: Social Frailtymentioning
confidence: 99%